Analysis of Pulmonary Tuberculosis Control Program Implementation at Tanah Baru Community Health Care, Depok Baru - Elysia Rahmatul Fitri, Asti; Lutfiah Rahmayanti, Verina; Alya Azis, Arkanaya; Nurcandra, Fajaria; Apriningsih, Apriningsih (Jurnal Kesehatan Manarang, 2025)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis that remains a global problem. In response to the burden of TB, the Indonesian government has established the TB Elimination Target for 2030. Primary health centers play a crucial role in implementing TB elimination strategies in Indonesia through effective and sustainable essential health services. This qualitative study, using a rapid assessment test design, aims to explore the tuberculosis control program in the Community Health Center (Puskesmas) Tanah Baru area more deeply. Data were collected through observation techniques and in-depth interviews with selected informants. This study involved seven informants selected through purposive sampling based on their roles and relevance to the TB program, including the Head of the P2P Program at the City Health Office, the Head of the TB Program at the City Health Office, the Head of the Puskesmas, the Puskesmas TB Program Holder, a Puskesmas nurse, the Head of Kapitu, and positive TB patients. Data analysis was conducted using the concept of triangulation of sources and methods. The results showed that the input and process components in the Puskesmas Tanah Baru TB control program were optimal. The implementation of promotive programs in the form of counseling, preventive programs such as screening, contact investigation, and provision of TPT, as well as curative programs, has been carried out according to national standards. Regarding the output component, the coverage of health services for people suspected of TB and the successful treatment of TB cases have reached the target. However, the overall coverage of TB case treatment has not yet met the predetermined target. The results of the TB control program at Puskesmas Tanah Baru largely meet the established indicators, although community stigma remains a significant obstacle to TB control efforts. Promotive and educational programs in the Puskesmas Tanah Baru area should be strengthened to reduce stigma within the community.